Analysis of "Nasyid Ibadallah" The Composition of Achmad Asrori Al-Ishaqi; A Hans Robert Jauss Literary Reception Study - 'Athiyyah, Avita Aniqotul; Mustofa, M. Lutfi (Jurnal Sastra Indonesia, 2024)
This study was conducted to describe the responses of UIN Maulana Malik Ibrahim Malang students to "Nasyid Ibadallah," describing the readers' expectation horizon towards "Nasyid Ibadallah," and know the factors of differences in responses and readers' expectation horizon. This research method uses a descriptive type of qualitative research by describing the concept of readers' expectation horizon by Hans Robert Jauss' perspective literary reception theory.  The data collection techniques are listening, interviewing, and note-taking. Data analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The primary data source is "Nasyid Ibadallah," composed of KH. Achmad Asrori Al-Ishaqi is presented to readers through the YouTube channel "Pendosa Berkhidmah" with the video title "Ibadallah, very melodious and full of meaning 2019, which lasts 08 minutes 01 seconds. At the same time, secondary data sources come from previous studies that are still relevant. The results of this study reveal that there are 24 responders, with a calculation of 18 responders responding positively and six responders responding negatively to the intrinsic elements of the literary work "Nasyid Ibadallah," resulting in 5 readers with a calculation of 4 responders who understand and one responder who does not understand the literary work based on the experience read, the difference in response is caused by education and previous literary experience. Most readers' expectations aligned with reality after reading "Nasyid Ibadallah." The diverse assessments reflect the readers' freedom in assessing literary works. The benefits of understanding readers' receptions and expectations of "Nasyid Ibadallah" include identifying educational and experiential factors that influence responses and increasing appreciation of religious literature.